A Bifunctional Metal–Organic Framework: Striking CO2‐Selective Sorption Features along with Guest‐Induced Tuning of Luminescence. Issue 8 (1st June 2016) - Mukherjee, Soumya; Desai, Aamod V.; More, Yogeshwar D.; Inamdar, Arif I.; Ghosh, Sujit K.
Abstract: A phenanthroline‐functionalized Cd II aminoterephthalate [Cd(NH2 ‐bdc)(phen)] n (NH2 ‐bdc=2‐aminobenzenedicarboxylic acid, phen=1, 10‐phenanthroline) metal–organic framework (MOF) displays CO2 ‐selective adsorption properties and photoluminescence induced by phenolic guests. The inherently guest‐free, rigid amine‐rich framework exhibits substantial CO2 ‐selective adsorption at ambient temperatures (both at 273 and 298 K) over other flue gases like N2, CH4, O2, Ar and H2, with a high isosteric heat of adsorption at zero coverage (Δ H ads ≈34 KJmol −1 ). Moreover, the fluorescent phenanthroline guest introduced to the MOF results in an excellent photoluminescence signature, which can serve as a marker for tuning phenolic‐guest‐induced luminescence. This marks the first report of observing distinct fluorescence responses to differentially functionalized phenolic analytes, in the domain of coordination polymer materials. Abstract : Pay your gas and light utilities ! A mixed‐linker strategy was used to synthesize a two‐dimensional Cd II ‐based luminescent metal–organic framework (LMOF). Owing to its primary‐amine‐rich Lewis basic voidspace, it exhibits selective CO2 uptake over flue gases, while its highly luminescent constituent linkers generate a dually tunable luminescent response that can serve to detect different phenolic species.